<h3>T
he probability that he pulls out either a black or white sock, puts it back and then pulls out a brown sock is ![(\frac{22}{169} )](https://tex.z-dn.net/?f=%28%5Cfrac%7B22%7D%7B169%7D%20%29)
</h3>
Step-by-step explanation:
Here , as given the total number of:
White Socks = 16
Brown Socks = 4
Black socks = 6
So, the total number of socks in the drawer = 16 + 4 + 6 = 26 socks
Now, the probability of picking a sock either a black or white sock is
![= \frac{\textrm{Total number of black + white sock}}{\textrm{The total number of socks}} = \frac{16+6}{26} = \frac{22}{26} = \frac{11}{13}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B%5Ctextrm%7BTotal%20number%20of%20black%20%2B%20white%20sock%7D%7D%7B%5Ctextrm%7BThe%20total%20number%20of%20socks%7D%7D%20%20%3D%20%5Cfrac%7B16%2B6%7D%7B26%7D%20%20%3D%20%5Cfrac%7B22%7D%7B26%7D%20%20%3D%20%5Cfrac%7B11%7D%7B13%7D)
Also, the picked sock is <u>replaced</u>. So, now the total socks are same = 26.
the probability of picking a brown sock is
![= \frac{\textrm{Total number of brown sock}}{\textrm{The total number of socks}} = \frac{4}{26} = \frac{2}{13}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B%5Ctextrm%7BTotal%20number%20of%20brown%20sock%7D%7D%7B%5Ctextrm%7BThe%20total%20number%20of%20socks%7D%7D%20%20%3D%20%5Cfrac%7B4%7D%7B26%7D%20%20%3D%20%5Cfrac%7B2%7D%7B13%7D)
Now, since both events are <u>independent events</u> , so the combined probability is given as:
P (E) = ![(\frac{11}{13} )\times (\frac{2}{13} ) = (\frac{22}{169} )](https://tex.z-dn.net/?f=%28%5Cfrac%7B11%7D%7B13%7D%20%29%5Ctimes%20%28%5Cfrac%7B2%7D%7B13%7D%20%29%20%3D%20%28%5Cfrac%7B22%7D%7B169%7D%20%29)
Hence, the probability that he pulls out either a black or white sock, puts it back and then pulls out a brown sock is ![(\frac{22}{169} )](https://tex.z-dn.net/?f=%28%5Cfrac%7B22%7D%7B169%7D%20%29)